Frontal sinus inverted papilloma managed with Draf III. Issue 8 (22nd August 2020) - Al Mahdi, Mohammed Jihad; Asiri, Mohammed; Pharaon, Majed; Mubark, Ali
Abstract: Inverted papilloma (IP) is a rare benign tumor that originates from nasal and paranasal sinus mucosa. Although it is considered a benign lesion, it is locally aggressive and has risk between 7 and 15% for malignant transformation. The management of frontal sinus (FS) IP is still challenging due to its rarity and local invasiveness. We report a rare case of IP originating from FS, and to review the literature to delineate the possible surgical strategy. A 52-year-old male presented with long-standing history of bilateral nasal obstruction and left eye proptosis. Sinus navigation computed tomography showed soft tissue density occupying frontal, ethmoid, right sphenoid sinuses with extension to nasal cavities, postnasal space and left orbital space plus erosive bony changes. Transnasal endoscopic biopsy suggested IP the lesion was completely resected by Draf III procedure. After 1 month of the surgery, the patient is doing well with no complaints.